2001
DOI: 10.2165/00007256-200131090-00004
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Demands of Running During Long Distance Runs and Triathlons

Abstract: The aim of this review article is to identify the main metabolic factors which have an influence on the energy cost of running (Cr) during prolonged exercise runs and triathlons. This article proposes a physiological comparison of these 2 exercises and the relationship between running economy and performance. Many terms are used as the equivalent of 'running economy' such as 'oxygen cost', 'metabolic cost', 'energy cost of running', and 'oxygen consumption'. It has been suggested that these expressions may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 75 publications
1
38
0
7
Order By: Relevance
“…During triathlon, performance depends on classical endurance qualities (Bentley et al, 2002;Hausswirth & Lehénaff, 2001), such as the maximum aerobic capacity, the aerobic-anaerobic threshold, and the efficiency of each locomotion mode. In an Olympic triathlon, the distance in each locomotion mode is for swimming, 1.5 km; cycling, 40 km; and running, 10 km.…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation
“…During triathlon, performance depends on classical endurance qualities (Bentley et al, 2002;Hausswirth & Lehénaff, 2001), such as the maximum aerobic capacity, the aerobic-anaerobic threshold, and the efficiency of each locomotion mode. In an Olympic triathlon, the distance in each locomotion mode is for swimming, 1.5 km; cycling, 40 km; and running, 10 km.…”
Section: %mentioning
confidence: 99%
“…During the last decade, triathlon, involving successive swimming, cycling, and running sessions, has become one the most popular multidisciplinary event. Studies focusing on factors affecting performance during a triathlon have clearly identified differences with single performance, indicating that the effect of previous locomotion mode on subsequent exercise was the main factor explaining changes in performance (Bentley, Millet, Vleck, & McNaughton, 2002;Bernard et al, 2007;Hausswirth & Lehénaff, 2001). Therefore the adaptation of triathletes must be considered as unique and relatively specific to the constraints activity (race profile, swim-cycle and cycle-run transitions, intensity, and exercise duration).…”
mentioning
confidence: 99%
“…[8,9] Triathlon performance has been studied from numerous perspectives by a number of research groups over approximately the same period that the sport has grown. Research has investigated physiological [1,10,11,12,13,14] , biomechanical [15,16,17] , training [16,18,19,20] , nutritional [21] or medical [22] aspects of triathlon performance. Although Ironman triathlon is a relatively new ultra-endurance event, recently elite Ironman triathletes appear to have reached their performance limits [2,23] as has been observed in more traditional sports such as marathon running where performance times have plateaued.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed as skeletal muscle damage during an ironman competition mostly result from eccentric contractions, mainly related to the marathon segment of the race [157], it can be argued that creatine may be effective in preventing eccentric induced muscle injury. In fact exhaustive exercises involving eccentric contractions, as in triathlon competition, lead to more pronounced muscle damage than strenuous exercises involving concentric contractions [158].…”
Section: Creatinementioning
confidence: 99%
“…In fact exhaustive exercises involving eccentric contractions, as in triathlon competition, lead to more pronounced muscle damage than strenuous exercises involving concentric contractions [158]. Nevertheless other mechanisms but eccentric damage may contribute to muscle damage during triathlon competition including excessive metabolic workload, muscle fatigue, depletion of intramuscular glycogen, and oxidative stress which are generally implicated in prolonged exercise-induced muscle fiber disruption [157,159,160]. The observed reduction in plasma activities of GOT and GPT (markers of liver injury) observed in triathletes after an ironman competition may suggest that creatine supplementation can enhance the metabolic efficiency of skeletal muscle preventing the metabolic workload on the liver which has a critical role on the contractile activity-induced skeletal muscle injury.…”
Section: Creatinementioning
confidence: 99%